STRATEGIES FOR DEVELOPMENT OF HOTEL ENTERPRISES IN CONDITIONS OF MARKET INSTABILITY - KUDRYAVTSEV, Vladislav; PROKOPENKO, Natalia; KOVALENKO, Natalia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Modern hotel businesses face numerous challenges associated with market instability caused by economic, social and political changes. This instability is manifested in fluctuations in demand for tourist services, changes in consumer preferences, as well as increased competition in the market. In conditions of such uncertainty, enterprises are forced to adapt their development strategies in order to maintain competitiveness and efficiency. One of the key problems is the lack of flexibility of traditional strategies, which does not allow enterprises to quickly respond to changes in the market situation. This is caused not only by external factors, but also by internal limitations, such as insufficient innovation, poor adaptation to new technologies and lack of resources. As a result, many hotels lose opportunities to optimize operating costs and improve the quality of customer service. The article provides a detailed analysis of modern hotel enterprise development strategies aimed at adapting to dynamic changes in the market environment. The article describes the key factors affecting the hotel business in conditions of market instability, and also formulates recommendations for increasing competitiveness. The impact of economic, political, socio-cultural and technological factors on the functioning of hotel business enterprises is considered. In particular, it is determined that economic conditions, such as the level of inflation and exchange rate changes, directly affect the demand for hotel services. Political stability is an important element that forms consumer trust, while socio-cultural trends, in particular, increasing attention to environmental friendliness, require enterprises to adapt their services. Technological innovations, including process automation and digital marketing, also play a critical role in increasing business efficiency. The results of the study indicate that hotel business enterprises that implement innovative technologies and focus on consumer needs have higher chances of successfully adapting to changing market conditions. The article also contains practical recommendations for implementing development strategies that help increase the sustainability of hotels and ensure their competitiveness in difficult economic realities.